CIRCULATING HAEMOGLOBIN LEVELS AND THE RISK OF ATHEROSCLEROSIS IN ASIAN INDIAN POPULATIONS. Issue 1 (2015) - Patel, Jeetesh V.; Flinders, Paul J.; Vyas, Avni; Glover, Imogen; Rajan, Avithra J.; Prabhakaran, Dorairaj; Bhatnagar, Deepak; Reddy, K. Srinath; Mackness, Michael I.; Cruickshank, J. Kennedy; Hughes, Elizabeth A.; Durrington, Paul N.
No abstract available